Making Student Loans Work in Africa - Johnstone, D. Bruce (International Journal of African Higher Education, 2016)
Cost-Sharing—meaning the shift of a portion of the costs of higher education (including the costs of student living) that may once have been borne predominantly or even exclusively by governments, or taxpayers, to parents and students—has been deeply contested, but found to be financially necessary (and according to many analysts more equitable) in more and more countries, including in Sub-Saharan Africa. Student loans have been part of this process, allowing students the opportunity to invest in their own further educations, placing needed revenue in the hands of students supposedly at less cost to taxpayers than outright grants (presuming loan recovery), and providing colleges and universities (again presuming loan recovery) with revenue that would not be forthcoming from governments. However, African student loan programs have been largely unsuccessful at providing significant net revenue supplementation: that is, after covering the cost of capital as well as the costs of originating, servicing, and collecting plus covering the substantial costs of defaults. This essay analyzes some of these problems and suggests some principles for making student loans work better in Africa. Le partage des coûts – c’est-à-dire le transfert aux parents et étudiants d’une partie du coût de l’enseignement supérieur (y compris le coût de la vie), qui était auparavant pris en charge majoritairement ou même exclusivement par le gouvernement, ou plutôt les contribuables– a été fortement contesté mais est devenu nécessaire (et selon de nombreux analystes est plus équitable) dans un nombre croissant de pays, notamment en Afrique sub-saharienne. Les prêts étudiants font partie intégrante de ce processus, donnant aux étudiants l’opportunité d’investir dans leur propre éducation, en mettant les revenus nécessaires entre les mains des étudiants, en principe à moindre coût pour le contribuable que les bourses (en présumant le remboursement du prêt), et fournissant aux établissements d’enseignement supérieur (toujours en présumant le remboursement du prêt) des revenus qui ne proviennent pas des gouvernements. Cependant, les programmes de prêts étudiants en Afrique ont largement échoué à fournir d’importants revenus complémentaires, une fois couverts le coût du capital ainsi que les frais de dossier, de service, de collection, et le coût considérable des défauts de paiement. Cet essai analyse certains de ces problèmes et propose quelques principes pour que les prêts étudiants fonctionnent mieux en Afrique.